The Relationship Between Age and Clinical Manifestations and COVID-19 Severity in Bengkulu in 2020 - Suryani, Utari Hartati; Triana, Dessy; Ambarsarie, Riry; Zainuddin, Zayadi; Massardi, Nikki Aldi; Voca, Begumratu; Putri, Dia Triyani (International Journal Labs, 2023)
The infectious disease COVID-19 caused by the SARS-CoV-2 virus can infect all age groups. The symptoms that arise can vary from no symptoms to severe and critical symptoms. Differences in clinical symptoms can occur due to differences in the distribution, maturation and function of the SARS-CoV-2 virus receptors. These clinical symptoms will determine the severity of COVID-19. This study aims to analyze the relationship between age and clinical symptoms and the severity of COVID-19 in Bengkulu Province in 2020. This study used an observational analytic study with a cross-sectional design. Samples were taken using a consecutive sampling technique and a total of 109 subjects were obtained who were COVID-19 patients in Bengkulu Province from March to December 2020. Assessment of clinical symptoms used COVID-19 epidemiological investigations. The degree of severity is determined based on the Guidelines for the Prevention and Control of COVID-19 by the Ministry of Health of the Republic of Indonesia. The relationship between the two variables was analyzed using the Spearman Rank test. The results of this study indicate that there is a significant relationship between the age factor of COVID-19 patients in determining the severity of COVID-19 (p=0.000; p <0.05).